2012
DOI: 10.1590/s0101-28002012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of training at ventilatory threshold on cardiopulmonary and functional capacity in overweight patients with chronic kidney disease

Abstract: Os autores declaram a inexistencia de conflitos de interesse. Palavras-chave: Doença Renal Crônica. Obesidade. Exercício. Terapia por Exercício. effectively applied for prescribing exercise intensity in this particular group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
2
24
0
3
Order By: Relevance
“…More importantly, the workload at those exercise intensities increased 16.7 % at VT and 15.3 % at RCP, which translates into improvements in the metabolic efficiency to sustain a greater workload and a potentially better tolerance for daily activities. This result was corroborated by improvements in the functional tests related to aerobic capacity, particularly the 6-min walk test and 2-min step test; similar to other reports, these values were in general below the levels expected for sedentary healthy subjects [18,24,25].…”
Section: Discussionsupporting
confidence: 87%
“…More importantly, the workload at those exercise intensities increased 16.7 % at VT and 15.3 % at RCP, which translates into improvements in the metabolic efficiency to sustain a greater workload and a potentially better tolerance for daily activities. This result was corroborated by improvements in the functional tests related to aerobic capacity, particularly the 6-min walk test and 2-min step test; similar to other reports, these values were in general below the levels expected for sedentary healthy subjects [18,24,25].…”
Section: Discussionsupporting
confidence: 87%
“…Unlike reports which focused only on the views of nephrologists [18,20] or on haemodialysis staff [21,22], this study aimed to ascertain the practices of the wider renal MDT involved in caring for patients at all stages of the CKD trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study were confirmed by Aoike DT et al The decrease in blood pressure due to mild/moderate aerobic exercise has been well established both in normotensive and hypertensive individuals as well as in chronic kidney disease patients. Aerobic training lowers blood pressure by reducing peripheral vascular resistance due to the improvement of endothelium-mediated vasodilatation, attenuation of increased sympathetic nervous system activity and vascular remodeling [38]. On the other hand, The results of current study not went will with Headley S et al Exercise had no effect upon either resting or ambulatory blood pressure in chronic kidney disease patients because blood pressure of the patients was already very well controlled by antihypertensive medications [39].…”
Section: Discussionmentioning
confidence: 48%